2020
DOI: 10.2478/johr-2020-0010
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Ethylene Synthetic Inhibitors in Regulating the Senescence of Cut Carnations through Membrane Integrity Maintenance

Abstract: Postharvest senescence is a critical problem of carnation cut flowers, limiting their transportation and subsequent marketing chain. This study was designed to assess whether the application of 1-methylcyclopropene (1-MCP), silver nanoparticles (AgNPs), and nitric oxide (NO) released from donor sodium nitroprusside (SNP) could prolong the vase life of cut carnations through an influence on the physiological and biochemical mechanisms involved in aging process. 1-MCP was used in the concentrations of 0, 100, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Furthermore, increasing the shelf life and keeping the fresh weight of damask rose flowers in response to 1-MCP treatment may be attributed to its role as an ethylene action inhibitor that irreversibly and competitively acts in blocking the ethylene receptor and, therefore, inhibits the flower senescence [ 13 ]. Extending the flower life through maintaining the fresh weight and RWC due to 1-MCP has been reported [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, increasing the shelf life and keeping the fresh weight of damask rose flowers in response to 1-MCP treatment may be attributed to its role as an ethylene action inhibitor that irreversibly and competitively acts in blocking the ethylene receptor and, therefore, inhibits the flower senescence [ 13 ]. Extending the flower life through maintaining the fresh weight and RWC due to 1-MCP has been reported [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this connection, 1-MCP effectively decreased ethylene production and markedly delayed petal senescence in dahlia flowers, suggesting the involvement of ethylene in flower senescence [ 21 ]. Additionally, 1-MCP application significantly decreased the activity of ACS and ACO, key enzymes in the ethylene production pathway and, therefore, extending the postharvest life through downregulating the ethylene production in orchids [ 75 ] and carnations [ 22 ]. Furthermore, inhibiting ethylene synthesis by 1-MCP treatment slows down senescence and retards the senescence-induced destructions of phenolics [ 16 ], which supports our results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be hypothesized the inhibitory effect of NO on ET biosynthesis in this process in the aforementioned ways. SNP treated cut roses exhibited decreased ACO activity and ET production (Liao et al, 2013) and cut carnivoles showed increased longevity in parallel with a decrease in ACS activity (Hassan et al, 2020). Furthermore, involvement of EIN2, which is a positive regulator of ET-induced senescence, in NO-induced early leaf senescence was also proved in Arabidopsis (Niu and Guo, 2012).…”
Section: -Pratap-singh-9780128187975mentioning
confidence: 88%